Cotidiano na velhice em Parintins/AM: concepções de participantes do centro de convivência do idoso “Pastor Lessa” - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
When we return to the study on old age, let's point out that the process of population aging is worldwide. Longevity is a conquest of society, but at the same time it is not a guarantee of a full life of satisfaction and of human needs assured to all the elderly. In the perspective of understanding how the elderly live in their time of old age in Parintins / AM, the present study had the general aim of revealing the daily life of the elderly participants in the "Pastor Lessa" In the municipality of Parintins. For this, the specific objectives were: To identify the economic and social activities carried out by the elderly before old age and in old age; Verify with the elderly people the activities related to them in the said Center; Aiming the view of the elderly about their old age. The subjects of the research were elderly people participating in the "Pastor Lessa" Elderly Living Center. From the universe of 174 elderly, a representative and nonprobabilistic sample was selected from 18 (12 elderly and 6 elderly), a total of 10% of the presented universe. The study was based on bibliographical, documentary and field research being of qualitative nature of an explanatory approach and based on the method of content analysis. As instrument and technique of data collection were used semistructured form, field diary and free observation. The operation of the collection of information was carried out in Parintins, in the premises of the Elderly Center for the Elderly "Pastor Lessa". The results of this research pointed out that the elderly people of the JRC in question, although positive and negative changes have operated in their lives with the arrival of old age, can live satisfactorily the old age in Parintins, as well, showed that these people have a A vast conception of old age, meeting what it really is - a condition of human and multidimensional nature experienced in distinct ways, including in relation to being an elderly woman or man. They also pointed out that the satisfaction of these elderly people is due to an ingredient most present in the daily life, the Center of Coexistence where the friendship and the coexistence between equals and different are extended. Therefore, the importance of implementation and continuity of actions and services of social assistance to the elderly in Parintins for the purpose of living good old age.
Keywords: Velhice; Cotidiano; Assistência social; Centro de convivência; Old age; Daily; Social assistance; Center of coexistence; CIENCIAS SOCIAIS APLICADAS: SERVICO SOCIAL